Comparing point shear wave elastography (ElastPQ) and transient elastography for diagnosis of fibrosis stage in non‐alcoholic fatty liver disease. Issue 1 (29th July 2019) - Leong, Wai Ling; Lai, Lee Lee; Nik Mustapha, Nik Raihan; Vijayananthan, Anushya; Rahmat, Kartini; Mahadeva, Sanjiv; Chan, Wah Kheong
Abstract: Background and Aim: Transient elastography (TE) and point shear wave elastography (pSWE) are noninvasive methods to diagnose fibrosis stage in patients with chronic liver disease. The aim of this study is to compare the accuracy of the two methods to diagnose fibrosis stage in non‐alcoholic fatty liver disease (NAFLD) and to study the intra‐observer and inter‐observer variability when the examinations were performed by healthcare personnel of different backgrounds. Methods: Consecutive NAFLD patients who underwent liver biopsy were enrolled in this study and had two sets each of pSWE and TE examinations by a nurse and a doctor on the same day of liver biopsy procedure. The medians of the four sets of pSWE and TE were used for evaluation of diagnostic accuracy using area under receiver operating characteristic curve (AUROC). Intra‐observer and inter‐observer variability was analyzed using intraclass correlation coefficients. Results: Data for 100 NAFLD patients (mean age 57.1 ± 10.2 years; male 46.0%) were analyzed. The AUROC of TE for diagnosis of fibrosis stage ≥ F1, ≥ F2, ≥ F3, and F4 was 0.89, 0.83, 0.83, and 0.89, respectively. The corresponding AUROC of pSWE was 0.80, 0.72, 0.69, and 0.79, respectively. TE was significantly better than pSWE for the diagnosis of fibrosis stages ≥ F2 and ≥ F3. The intra‐observer and inter‐observer variability of TE and pSWE measurements by the nurse and doctor was excellent with intraclass correlation coefficient > 0.96. Conclusion: Transient elastography was significantly better than pSWE for the diagnosis of fibrosis stage ≥ F2 and ≥ F3. Both TE and pSWE had excellent intra‐observer and inter‐observer variability when performed by healthcare personnel of different backgrounds.